Survei Batimetri Menggunakan Wahana USV (Unmanned Surface Vehicle) pada Perairan Dangkal dan Uji Kualitas Data Sesuai Standar IHO S44 Tahun 2022: (Studi Kasus Embung Sungai Nanam, Kabupaten Solok) - Fajrin, Fajrin; Afandi Haris; Dwi Arini; Aswir Premadi (Jurnal Sains dan Ilmu Terapan, 2025)
A bathymetric survey is an activity aimed at depicting the depth contour lines of a water body, encompassing measurement, data processing, and visualization stages. Conducting a bathymetric survey in shallow waters, such as reservoirs, estuaries, lakes, dams, or sedimentation areas, often presents challenges when using large vessels. One of the technologies for performing bathymetric surveys in shallow waters is the use of an Unmanned Surface Vehicle (USV), which facilitates data collection while offering flexibility, efficiency, and effectiveness. The study aims to produce a bathymetric map from bathymetric measurement data using a USV (Unmanned Surface Vehicle) corrected with real-time tidal data and to determine the data quality order according to the IHO (International Hydrographic Organization) S44 Edition-6 Standard of 2022.